Detection and prevalence of antimicrobial resistance genes in multidrug-resistant and extensively drug-resistant Staphylococcus and Streptococcus species isolated from raw buffalo milk in subclinical mastitis - Md. Shahidur Rahman Chowdhury; Hemayet Hossain; Md. Bashir Uddin; Md. Matiur Rahman; Ferdaus Mohd Altaf Hossain; Md. Rafiqul Islam; M. Nazmul Hoque; Md. Masudur Rahman; Md. Mukter Hossain; Md. Mahfujur Rahman (PLoS ONE, 2025)
Subclinical mastitis (SCM) poses a significant threat to the global dairy industry, particularly in Bangladesh, where it remains a major constraint in buffalo dairy farming. The rising prevalence of antimicrobial resistant pathogens complicates disease management, resulting reduced milk yield, increased veterinary expenses, compromised animal welfare and potential risk to public health. This study investigated the prevalence and resistance profiles of multidrug-resistant (MDR) and extensively drug-resistant (XDR) Staphylococcus and Streptococcus species in raw buffalo milk from SCM cases in Bangladesh. A total of 1,540 quarter milk samples from 385 buffaloes were analyzed, revealing SCM prevalence rates of 67.9% (1046/1540; 95% CI: 65.6–70.3) at the quarter level and 80.8% (311/385; 95% CI: 76.5–84.6) at the animal level. Notable regional variations were observed, with Gowainghat showing the highest prevalence (88.1%; 141/160). This study did not identify any biologically plausible risk factors for the occurrence of SCM in buffalo. The Modified Whiteside Test and California Mastitis Test confirmed SCM, with culture and biochemical tests identifying 789 (51.2%) Staphylococcus spp. and 424 (27.5%) Streptococcus spp. isolates. Polymerase Chain Reaction (PCR) analysis indicated that 72.7% (456/627) of Staphylococcus isolates were Staphylococcus aureus, while the predominant Streptococcus species included Streptococcus uberis (32.3%) and Streptococcus dysgalactiae (14.9%). Resistance gene detection revealed a high prevalence of antimicrobial resistant genes (ARGs), particularly aac-3(iv) and tetA, across different buffalo quarters and habitats. Antibiogram profiling demonstrated high susceptibility to tetracycline (80.9; 83.1) and trimethoprim-sulfamethoxazole (87.4; 81.9), while significant resistance was noted against ampicillin (88.8; 87.1) and nalidixic acid (68.1; 62.1). MDR was observed in 76.4% (479/627) of Staphylococcus spp. and 67.3% (167/248) of Streptococcus spp. isolates, with 10.37% (65/627) and 10.48% (26/248) classified as possible XDR, respectively. These findings explored high antimicrobial resistance level among Staphylococcus and Streptococcus species in subclinical mastitis, highlighting the need for improved management practices and surveillance to mitigate public health risks posed by contaminated milk.